2019
DOI: 10.1093/ageing/afz035
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of applying the new EWGSOP2 guideline instead of the former EWGSOP guideline for sarcopenia case finding in older patients

Abstract: Introduction we examined the consequences of applying the new EWGSOP2 algorithm for sarcopenia screening instead of the former EWGSOP algorithm (EWGSOP1) in geriatric inpatients. Methods the dataset of our formerly published Sarcopenia in Geriatric Elderly (SAGE) study includes 144 geriatric inpatients (86 women, 58 men, mean age 80.7±5.6 years) with measurements of gait speed, handgrip strength and appendicular muscle mass b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 29 publications
8
73
3
3
Order By: Relevance
“…The prevalence of low functional status was also numerically higher in men (65%) than in women (40%), but low gait speed was found among similar proportions of patients (60% vs. 55%). Some sex-related differences in the prevalence of sarcopenia and its outcome have been reported (19,20,24). It appears that in men, chronic diseases lead to a more dynamic decline in muscle mass.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence of low functional status was also numerically higher in men (65%) than in women (40%), but low gait speed was found among similar proportions of patients (60% vs. 55%). Some sex-related differences in the prevalence of sarcopenia and its outcome have been reported (19,20,24). It appears that in men, chronic diseases lead to a more dynamic decline in muscle mass.…”
Section: Discussionmentioning
confidence: 96%
“…However, the previous studies have used different diagnostic criteria not allowing for a direct comparison with our study using EWGSOP2 criteria. One study has compared the prevalence of sarcopenia using both EWGSOP1 and 2 algorithms showing a slightly lower prevalence of 27.7 vs.18.1% when using EWG-SOP2 criteria (20).…”
Section: Discussionmentioning
confidence: 99%
“…[26]. In geriatric patients, the literature is conflicting showing higher [27][28][29] or equal [30,31] rates of sarcopenia with the 2010 compared to the 2019 definition. The predictive utility for complications seems to be different for the 2010 and 2019 definition-in chronic obstructive pulmonary disease both definitions performed well, whereas in the UK biobank cohort the 2010 definition was superior in predicting poorer health outcome.…”
Section: Discussionmentioning
confidence: 99%
“…EWGSOP2-defined sarcopenia prevalence was lower than that defined using EWGSOP-1 criteria due to the difference in diagnostic factors to detect sarcopenia. Reiss et al reported a sarcopenia prevalence of 18.1% using the EWGSOP2 criteria versus a 27.7% prevalence with the EWGSOP criteria in 144 geriatric patients [ 11 ]. Similarly, in a study with 501 subjects, Locquet et al observed a prevalence of sarcopenia of 7.4% and 13.6% for EWGSOP2 and EWGSOP, respectively [ 12 ].…”
Section: Sarcopeniamentioning
confidence: 99%